IGF1R inhibition and PD-1 blockade improve anti-tumor immune response in epithelial ovarian cancer - Somri-Gannam, Lina; Meisel-Sharon, Shilhav; Hantisteanu, Shay; Bar-Noy, Tomer; Sigal, Emiliya; Groisman, Gabriel; Hallak, Mordechai; Werner, Haim; Bruchim, Ilan (Frontiers in Oncology, 2024)
IntroductionThe insulin-like growth factor (IGF) system plays a key role in regulating growth and invasiveness in epithelial ovarian cancer (EOC) and is considered a promising therapeutic target. EOC is an immunosuppressive disease, although there are limited data about the involvement of the IGF1R system in the anti-tumor immune response in the EOC microenvironment.MethodsIn the current study, we hypothesized that IGF 1 receptor (IGF1R) involvement in the maturation of dendritic cells (DC) with the co-inhibition of IGF1R and PD-1 would affect the EOC microenvironment.ResultsWe found that DC pretreated with IGF1R inhibitor resulted in fewer EOC cells. Moreover, in vivo experiments conducted with an EOC mouse model, with anti-PD-1/IGF1R combined, resulted in lower tumor weight compared to individual treatments. Additionally, anti-PD-1/IGF1R treatment increased DC by 34% compared with AEW-541 and 40% with anti-PD-1. The combined treatment increased CD8+ T-cell levels compared to AEW-541 alone. RNA-seq data analysis indicated that anti-PD-1/IGF1R led to a more potent immune response, as reflected by altered gene expression levels related to anti-tumor immune response, compared with either treatment alone.DiscussionThese findings provide novel evidence that IGF1R axis inhibition combined with PD-1 blockade may be an effective therapeutic strategy for selected EOC patient populations.